Autistic traits modulate conscious and nonconscious face perception - Stavropoulos, Katherine K M; Viktorinová, Michaela; Naples, Adam; Foss-Feig, Jennifer; McPartland, James C (Social neuroscience, 2018)
Difficulty with emotion perception is a core feature of autism spectrum disorder (ASD) that is also associated with the broader autism phenotype. The current study explored the neural underpinnings of conscious and nonconscious perceptions of affect in typically developing individuals with varying levels of autistic-like traits, as measured by the Autism Quotient (AQ). We investigated the relationship between autistic traits and face processing efficiency using event-related potentials (ERPs). In 20 typically developing adults, we utilized ERPs (the P100, N170, and P300) to measure differences in face processing for emotional faces that were presented either (a) too quickly to reach conscious awareness (16 ms) or (b) slowly enough to be consciously observed (200 ms). All individuals evidenced increased P100 and P300 amplitude and shorter N170 latencies for nonconscious versus consciously presented faces. Individuals with high AQ scores evidenced delayed ERP components. Nonconsciously perceived emotional faces elicited enhanced neural responses regardless of AQ score. Higher levels of autistic traits were associated with inefficient face perception (i.e., longer latency of ERP components). This delay parallels processing delays observed in ASD. These data suggest that inefficient social perception is present in individuals with subclinical levels of social impairment.
Keywords: mozek; mužské pohlaví; Male; Female; Humans; elektroencefalografie; autistická porucha; sociální percepce; Autistic Disorder; Brain; Neuropsychological Tests; lidé; emoce; ženské pohlaví; evokované potenciály; Evoked Potentials; Facial Recognition; Young Adult; neuropsychologické testy; Social Perception; Emotions; Electroencephalography; rozpoznání obličeje; mladý dospělý; Personality; osobnost